Don't count me out: erasure of ethnicity and ethnic groups from national censuses. - Livny, Avital (Journal of Ethnic & Migration Studies, 2026)
Existing theories of ethnic enumeration and violence focus on how censuses spark inter-ethnic conflict and allow for state predation of vulnerable groups. But these accounts overlook how ethnic demographics are also used to advocate for the vulnerable and hold states accountable for their mistreatment. From this perspective, there is far more danger in being un-counted – a sign that the state is destroying the paper trail to cover its eliminationist ambitions. I define four types of 'enumerative erasure' – both at the country-level and among groups – and amass a new database of changing enumerative practices, covering nearly 250 countries and over 8,000 distinct ethnic groups between 1900–2020. Across countries and groups alike, I find that the state's elimination of ethnic census data is systematically followed by more political discrimination and state-sponsored violence targeting ethnic groups. In contrast, starting to enumerate ethnic groups tends to offer more protection from state predation, even as it has been found to increase inter-group tensions. Taken together, these results indicate that enumerative erasure may serve as a credible warning sign of eliminationism aimed at vulnerable un-counted groups.